Platelet transfusion to reverse antiplatelet therapy before decompressive surgery in patients with intracranial haemorrhage. Issue 6 (14th August 2017) - Baschin, M.; Selleng, S.; Zeden, J.‐P.; Westphal, A.; Kohlmann, T.; Schroeder, H. W.; Greinacher, A.; Thiele, T.
Abstract : Background: Platelet concentrates (PC) are transfused to improve primary haemostasis before urgent neurosurgery in patients with intracranial haemorrhage (ICH) receiving antiplatelet therapy (APT). It is unresolved, whether PCs increase the risk for major cardio‐ and cerebrovascular adverse events. We evaluated a standardized transfusion regimen to reverse APT in patients with ICH who required decompressive neurosurgery. Methods: Analysed were consecutive patients between 2012 and 2014. The primary outcome was the frequency of new arterial thrombotic complications. The secondary outcome was the frequency of recurrent ICH. Results: Of 72 patients, 14 received acetylsalicylic acid and a P2Y12 inhibitor, 53 received acetylsalicylic acid and five clopidogrel. No acute coronary syndrome (95% CI: 0–5·07) and one ischaemic stroke occurred (1·4%; 95% CI: 0·25–7·46). In contrast, 26·4% of patients developed recurrent ICH (95% CI: 17·59–37·58). The risk of bleeding was significantly higher compared to the risk of arterial thrombosis ( P < 0·00001) and was increased for patients with chronic ICH (OR: 4·78; 95% CI: 1·57–14·55) and those receiving clopidogrel (OR: 2·78; 95% CI: 0·90–8·57). Conclusion: Platelet concentrate transfusion before cranial decompressive surgery in patients with ICH complicating APT showed a low risk for cardio‐cerebral thrombotic complications. However, the risk of rebleeding remains high, especially in patients with chronic ICH and those pretreated with clopidogrel.